2021
DOI: 10.9734/jpri/2021/v33i47b33172
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Genetic Alterations in Genes of Fibroblast Growth Factor Family and Their Possible Association with HNSCC

Abstract: Introduction: HNSCC is a type of cancer in the oral and pharynx region. Several mutations/variations are observed in these cancer phenotypes. Fibroblast growth factor belongs to the family of heparin binding growth factors. FGFs are multifunctional proteins with a wide variety of effects; they are most commonly mitogens. Their expression pattern correlates with invasion of HNSCC. Aim: To assess the genetic alterations in genes of the fibroblast growth factor family and their association with HNSCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Many studies have confirmed that FGFs are highly expressed in a variety of tumors, such as lung cancer [ 4 , 5 ], gastric cancer [ 6 ], and breast cancer [ 7 ], and promote tumor progression. However, few studies have reported the role of FGFs in cell carcinoma [ 8 ]. Here, we detected FGF3 in 40 cases of tongue squamous cell carcinoma and corresponding adjacent tissues by immunohistochemistry and found high expression levels of FGF3 were 90% in tumors and 12.5% in the surrounding tissues ( P < 0.01).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that FGFs are highly expressed in a variety of tumors, such as lung cancer [ 4 , 5 ], gastric cancer [ 6 ], and breast cancer [ 7 ], and promote tumor progression. However, few studies have reported the role of FGFs in cell carcinoma [ 8 ]. Here, we detected FGF3 in 40 cases of tongue squamous cell carcinoma and corresponding adjacent tissues by immunohistochemistry and found high expression levels of FGF3 were 90% in tumors and 12.5% in the surrounding tissues ( P < 0.01).…”
Section: Introductionmentioning
confidence: 99%